Stable linked genes for rust and powdery mildew resistance in wheat (Triticum aestivum) - TOMAR, S M S; MENON, M K; BOJAN, S; SINHA, V C (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted under field and greenhouse conditions for 4 years (8 seasons) during 2001-2005 to transfer stable linked genes for resistance to rust and powdery mildew in wheat (Triticum aestivunz L. emend. Fiori & Paot.). Nineteen bread wheat cultivars susceptible to leafrust, stem rust and powdery mildew were chosen for incorporating resistance genes, Lr19/Sr25, Sr36 and Pm6. Three backcrosses were given to the recurrent parents. The evaluation ofthe limited backcross lines along with their recurrent parents and some stocks with specific Lr genes under natural and artificial epiphytotic conditions revealed that they confer esistance to leafrust, stem rust and powdery mildew pathotypes prevailing in the Nilgiris. Eleven backcross lines were also tested in adult stage at New Delhi with a leafrust pathotype 778 virulent on Lr19. Backcross lines ’HD 2285*3/Cook*6/C 80-1’ and ’WH 147*3/Cook*6/C 80-1’ showed moderate susceptibility and ’Kalyansona*3/Cook*6/C80-1 " ’J24*3/Cook*6/C 80-1’ and ’PBW226*3/Cook*6/C80-1’ low susceptibility to 77-8 pathotype at adult stage. Remaining lines showed total freedom from leafrust infection. Results also indicated that pathotype 77-8 is avirulent on Lr26 and also to unknown genes carried by ’Lok l’ and.’UP 262’. Adult plant reaction of’NI 5439’, ’Kalyansona’ and ’WH 147’ further revealed that Lr19 virulent pathotype is non-aggressive. High degree of resistance to stem rust and powdery mildew exhibited by backcross Jines indicated that these carry the genes Sr36 and Pm6. The availability of a combination of resistance genes in background of adapted wheat cultivars win enhance their usability.